Ultraviolet Radiation Knowledge and Exposure Practices Among Serbian High School Students: Results of a Nationwide Survey - Slavica Malinović-Milićević; Gorica Stanojević; Elena Milićević; Dejan Doljak (Atmosphere)
The incidence of skin carcinoma has significantly increased among the Serbian population, with mortality rates among the highest in the world. Basic interventions can reduce the effects of ultraviolet radiation (UVR) exposure, especially in youth, and decrease incidence and morbidity. This study is the first cross-sectional nationwide research on knowledge, attitudes, and sun exposure practices among Serbian high school students. The results revealed that fewer than 5% of students can correctly interpret the sunburn effect of a given UV index, while sun protection strategies are infrequently adopted. Most students (55.97%) expressed favorable attitudes regarding tanning, while more than half (64.48%) reported moderately high and high exposure. Females are more likely than males to expose themselves to UVR, especially intentionally. Females use protection more than males, while even 62.65% of males use protection insufficiently. The most commonly used sun protective measures were sunscreen and shade. The results indicate the necessity for innovative and age-suitable education methods and age- and gender-directed awareness campaigns for skin cancer prevention and the promotion of sun safety. Specifically, campaigns aimed at females should focus on motivating reduced intentional exposure, while those targeting males should emphasize the consistent use of sun protection measures.